Seroprevalence and current infections of canine vector-borne diseases in Nicaragua - Springer, Andrea (2018)
Background: Vector-borne diseases constitute a major problem for veterinary and public health, especially in tropical regions like Central America. Domestic dogs may be infected with several vector-borne pathogens of zoonotic relevance, which may also severely compromise canine health. Methods: To assess the prevalence of canine vector-borne diseases in Nicaragua, 329 dogs from seven cities, which were presented to the veterinarian for various reasons, were included in this study. Dogs were examined clinically and diagnostic blood samples were taken for analysis of packed cell volume (PCV) and presence of microfilariae as well as antigen of Dirofilaria immitis and antibodies to Ehrlichia spp., Anaplasma spp. and Borrelia burgdorferi (sensu lato) by use of a commercially available rapid ELISA. To detect current infections, specific PCRs for the detection of E. canis, A. platys and A. phagocytophilum were carried out on blood samples of the respective seropositive dogs. Microfilaremic blood samples, as well as D. immitis antigen positive samples were further subjected to PCR and subsequent sequencing for filarial species identification. Results: Antibodies against Ehrlichia spp. were present in 62.9% of dogs, while Anaplasma spp. seroprevalence was 28. 6%. Antibodies against species of both genera were detected in 24.9% of dogs. Borrelia burgdorferi (s.l.) antibodies were not detected. Dirofilaria immitis antigen was present in six animals (1.8%), two of which also showed D. immitis microfilariae in buffy coat. In addition to D. immitis, Acanthocheilonema reconditum was identified by PCR and sequencing in two of four additional microfilaremic blood samples, which were tested negative for D. immitis antigen. Current E. canis infections as defined by DNA detection were present in 58.5% of Ehrlichia-seropositive dogs, while 5.3% of Anaplasma-seropositive dogs were PCR-positive for A. platys, 2.2% for A. phagocytophilum and 16.0% for both Anaplasma species. Current E. canis infection had a statistically significant negative impact on PCV, whereas no relationship between infection status and clinical signs of disease could be observed. Conclusions: These results indicate that canine vector-borne diseases are widespread in Nicaragua and that dogs may constitute a reservoir for human infection with E. canis, A. phagocytophilum and D. immitis. Thus, the use of repellents or acaricides to protect dogs from vector-borne diseases is strongly recommended.